IMPACT OF EMOTIONAL INTELLIGENCE ON EMPLOYEE PERFORMANCE WITH LOCUS OF CONTROL AS MODERATION VARIABLE (STUDY AT PT. TOR GANDA MEDAN) - Tapi Rondang Ni Bulan; Annisa Suvero Suhyar; Dear Sucy Rahmadhany (Institut Pendidikan Tapanuli Selatan, 2022)
This study aims to find out Emotional Intelligence to Employee Performance with locus of control as a moderation variable at PT. Tor Ganda Medan. Moderated Regression Analysis (MRA) research design is used as an analytical tool to determine the direction of the variables studied as well as justify how significant the influence of independent variables on dependent variables with the influence of moderation variables. The study used associative methods. The population of 162 people, with a sample of 115 respondents, was obtained using the slovin formula system. The results showed that Emotional Intelligence has a positive and significant effect on Employee Performance. The Locus of Control cannot moderate to the relationship between Emotional Intelligence and Employee Performance.